Excellent Transmittance Induced Phase Transition and Grain Size Modulation in Lead‐Free (1–x)(K0.5Na0.5)NbO3–xLaBiO3 Ceramics. Issue 6 (14th March 2016) - Yang, Zhenyu; Zhang, Xiaoshuai; Yang, Dong; Yang, Bian; Chao, Xiaolian; Wei, Lingling; Yang, Zupei
Abstract : A novel lead‐free excellent transmittance electro‐optic ceramics (1– x )(K0.5 Na0.5 )NbO3 – x LaBiO3 (KNN‐LB, x = 0.000, 0.005, 0.010, 0.015, 0.020, 0.025, 0.040, 0.060) were fabricated by traditional pressureless ceramics processing procedure. The effects of LaBiO3 dopant concentration x on the microstructure, phase transition, optical property, and electrical properties were studied systematically. The X‐ray diffraction results indicated that the KNN‐LB ceramics with x ≥ 0.025 have the pseudocubic phase. The morphology, density, and microstructure of the KNN‐LB ceramics were characterized by scanning electronic microscopy and optical microscopy. In particular, the KNN‐LB ceramics (0.05 mm thickness) with x = 0.025 exhibited the highest transmittance of 74.00% in the visible spectrum comparable to the 72.00% transmittance of the lead lanthanum zirconate titanate (PLZT 9/65/35 of 0.127 mm thickness). In addition, the related mechanism of transparency variation induced by phase transition and grain size modulation were discussed thoroughly. Finally, the dielectric and ferroelectric properties of as‐prepared KNN‐LB ceramics were also investigated to further clarify the relationship between transparency and relaxor behavior.